Youth extremism as a response to global threats? A threat-regulation perspective on violent extremism among the youth - Kaya, Ayhan; Tecmen, Ayşe; Troian, Jais (İstanbul Bilgi Üniversitesi, 2019)
Violent extremism is rising across the globe as indicated by the growing number of attacks conducted by terrorist organizations. It is known that violent extremism is carried out mainly by youth due to developmental specificities. Furthermore, recent evidence suggests that ideologically motivated violence stems from threat-regulation processes (i.e. aiming to restore significance, control and certainty). Nevertheless, few studies from the threat-regulation literature have focused on youth samples and on the political context in which radicalization processes occur. Here, we demonstrate that one driver of the surge in violent extremism might be globalization. To do so, we review the evidence that shows globalization increases perception of affiliative, economic and existential threats. In return, studies suggest that these kinds of threats promote violent extremism among youth samples. Therefore, we conclude that the threatening context generated by four decades of globalization might be a risk factor for youth extremism in the long run.
30 pages